Role of Corporate Governance in Mitigating Risk in Private Banks: An Empirical Study of ICICI Bank and Axis Bank - Gupta, Aanchal; Moolchandani, Ritika; Saini, Sanjay Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This empirical study conducts a comparative analysis of the role of corporate governance in risk mitigation for two leading Indian private sector banks, ICICI Bank and Axis Bank. In an era defined by financial volatility and multidimensional risks, robust governance frameworks have become indispensable for institutional resilience. The research investigates the core constituents of their governance—including independent board oversight, specialized risk committees, enterprise-wide Risk Appetite Frameworks (RAF), and a strong compliance culture—and evaluates their direct impact on key risk and financial metrics. The findings demonstrate a strong positive correlation between sophisticated governance mechanisms and enhanced risk outcomes. This is evidenced by superior financial indicators, including Capital Adequacy Ratios significantly exceeding regulatory mandates (16.33% for ICICI, 16.63% for Axis), low Gross NPA ratios (1.67% and 1.30% respectively), and high Provision Coverage Ratios ( 80%). Furthermore, both banks exhibit proactive governance by integrating Environmental, Social, and Governance (ESG) factors and advanced cybersecurity protocols into their strategic risk management. The study concludes that effective corporate governance is a critical strategic tool that directly translates into disciplined risk-taking, financial stability, and sustainable value creation, offering vital insights for policymakers, regulators, and banking practitioners aiming to fortify the Indian banking sector.